The Relationship between the Level of Nurse Knowledge and the Accuracy of the Assessment of the Glasgow Coma Scale in Head Injury Patients in the Emergency Room of Prof. Dr. H. Aloei Saboe Hospital, Gorontalo City - Lendy Kurniawan; Pipin Yunus; Fifi Ishak (Universitas Muhammadiyah Palu, 2026)
The Glasgow Coma Scale (GCS) is included in the primary survey carried out when a patient enters the emergency room which is usually assessed by the emergency room nurse and can prevent complications so that it requires a proper GCS examination. The purpose of this study was to determine the relationship between the level of knowledge of nurses and the accuracy of the assessment of the Glasgow Coma Scale in patients with head injuries in the emergency room of Prof. Dr. H. Aloei Saboe Hospital, Gorontalo City. Quantitative research method with a cross sectional study approach, the population in this study was all implementing nurses in the emergency room of Prof. Dr. H. Aloei Saboe Hospital, Gorontalo City, a research sample of 29 nurses with a total sampling technique, research instruments using knowledge questionnaires and GCS assessment observation sheets, data were analyzed by Chi-square test. The results of the study obtained the level of knowledge of nurses about the GCS assessment which was good knowledge as many as 19 nurses (65.5%) and sufficient knowledge as many as 10 nurses (34.5%), then the accuracy of the right GCS assessment was 21 nurses (72.4%) and inappropriate as many as 8 nurses (27.6%), and a p-value of 0.000 (? ? 0.05) was obtained. It can be concluded that there is a relationship between the level of nurse knowledge and the accuracy of GCS assessment in head injury patients in the emergency room of Prof. Dr. H. Aloei Saboe Hospital, Gorontalo City.